Evaluation of the role of aluminium sulfate of potash (KAl(SO₄)₂·12H₂O) in improving the dyeing properties and colour fastness of wool and cotton/viscose blends - Ghada Moftah Soufeljin; Hania Alaref Abureah (African Journal of Advanced Pure and Applied Sciences, 2025)
Dyeing with natural plants is a sustainable and environmentally friendly method compared to chemical dyes, which cause environmental pollution and consume large amounts of energy and harmful chemicals. This project aims to study the possibility of using natural plants, such as cloves, olive leaves, and indigo, to dye cotton and wool fabrics as a sustainable and environmentally friendly alternative to chemical dyes. This research evaluated the effect of aluminum potassium sulfate (alum) as a stabilizer on the color fastness of fabrics dyed with plant products, by conducting light exposure, washing, and dry and wet rubbing tests. The experiment included three main techniques: dyeing without a stabilizer, using a stabilizer before dyeing, and using a stabilizer after dyeing. The results showed that cloves and olive leaves achieved excellent results and high stability to light, washing, and dry and wet rubbing. Lightfastness results after exposure to sunlight for 80 and 100 hours showed readings of 7 and 8 on the blue wool color index for both cloves and olive leaves, respectively, and 4/5 and 5 on the gray color index for each, respectively. Indigo powder, however, did not produce positive results, with weak readings of 2/3 on the gray color index and 2 on the blue wool standard index. The results were similar in the wash fastness test, with the exception of blue indigo, which achieved better results in the wash test than the light test, while the dry rub test achieved better results than the wet rubbing test. The study concluded that natural dyes such as cloves and olive leaves achieve excellent results in terms of color fastness, light resistance, and washing, even without the use of chemical stabilizers. They produce stable colors that are stable to light, washing, dry rubbing, and wet rubbing, which are among the most important criteria for measuring textile product quality and are considered a safe alternative. It is natural for industrial dyes to cause huge environmental pollution.